Regression to death in Arabic poetry (Malik bin Al-Rayeb and Khalil Mutran as a model) - منصور العمري, حسين (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This research is based on the study of the phenomenon of dealing with death in Arabic poetry, from a limited angle through the following question: How did the Arab poet receive the state of death if he felt close to it, as this situation appeared in some ancient and contemporary poets, as the research focused on two poets: Malik ibn al-Rib in the old poetry when he felt his fate is sealed through his poem (Al-marthea), as well as the poet Khalil Matran of contemporary poets who felt the end of his time and how he dealt with death by seeking of the thing, so he was included through his verses in the poem (evening) until he reached the last moment, which is the moment of surrender to death.